The Importance of Developing the Professional Attitude of Science Teachers as Communicators and Facilitators in Student Learning in the Classroom - Rosabela, Alfina Eka; Mahardika, I Ketut; Syabrina, Najmah; Ainurrokhmah, Ulya ’ (Peneliti.net, 2024)
A teacher is a profession that has the task of educating and teaching students. The role of teachers is very important in educating the nation's children, especially in the field of science. Currently, science education in Indonesia is of low quality. One of the people who has contributed to the progress of science education is the science teacher. The professional nature of science teachers can also have an influence in advancing science education in Indonesia. The government is currently improving the quality of teachers in Indonesia, especially science teachers. A teacher not only masters the material and memorizes science, but a science teacher must also understand the phenomena that occur related to science. The purpose of this article is to challenge the role of science teachers as communicators and facilitators for students, as well as how to develop science teachers into professional teachers. The research method used is a qualitative method by collecting data from various sources, literature and also the internet. The expected result of this article is that science teachers will more easily understand the role of a good facilitator and communicator and how to develop this attitude in order to create effective and optimal learning.